Rate equations of polymerization reactions - Mezaki, Reiji (ChemTec Pub., 1997)
This book is a compilation from technical journals in both chemistry and chemical engineering. It covers rate expressions for polymerization reactions pertaining to the analysis, optimal design, and optimal operation of polymerization reactors.